Acceleration of wound healing by ultrasound activation of TiO2 in Escherichia coli‐infected wounds in mice. Issue 8 (10th August 2016) - Osumi, Koji; Matsuda, Sachiko; Fujimura, Naoki; Matsubara, Kentaro; Kitago, Minoru; Itano, Osamu; Ogino, Chiaki; Shimizu, Nobuaki; Obara, Hideaki; Kitagawa, Yuko
Abstract: Surgical site infections continue to be a common complication affecting surgical prognosis. Reactive oxygen species (ROS) are generated by ultrasound‐irradiated titanium dioxide (TiO2 ) (UIT). Although excessive ROS production can cause cell damage, ROS at physiological levels mediate beneficial cellular responses, including angiogenesis. This study investigated whether UIT can promote healing of Escherichia coli‐infected wounds. We used TiO2 and ultrasound irradiation using an ultrasonography machine at a frequency of 1.0 MHz and intensity of 0.4 W cm −2 . These levels are not bactericidal in vitro ; therefore, we could study the effect of UIT on E. coli survival without interference of ultrasound effects. The number of cluster of differentiation 31‐positive blood vessels, which are indicative of angiogenesis, was decreased by bacterial infection, and increased at the wound edges in the UIT‐treated infected wounds, suggesting upregulation of neovascularization by UIT. Although UIT treatment did not decrease E. coli survival in vivo, it promoted healing of the infected wounds as evidenced by a significant decrease in the wound area in the UIT‐treated mice. Our findings demonstrate that UIT promotes wound healing in surgical site infections and suggest beneficial use of the UIT‐based approach as a novel therapeutic method to treat infected surgical wounds. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 2344–2351, 2017.